Protective effects of thrombomodulin on microvascular permeability after subarachnoid hemorrhage in mouse model. (23rd July 2015) - Xu, T.; Zhang, W.-G.; Sun, J.; Zhang, Y.; Lu, J.-F.; Han, H.-B.; Zhou, C.-M.; Yan, J.-H.
Highlights: There is a vasogenic brain edema after SAH as shown by MRI. Apoptosis/inflammation in endothelium induced enhanced vascular permeability. Thrombomodulin preserved vascular integrity via activated protein C/PAR-1 through blocking p38MAPK-p53/NF-κB pathway. Abstract: The enhanced vascular permeability is a major early brain injury following subarachnoid hemorrhage (SAH). However, its mechanism is not clear yet. In this work, we explored its potential mechanism and investigated the roles of thrombomodulin (TM) in maintaining microvascular integrity after SAH. SAH models were established in adult male ICR mice (28–32 g) by endovascular perforation. TM was immediately administered by femoral vein injection following SAH. The brain water content, Evans Blue content and neurological functions were evaluated. Brain edema was also detected by magnetic resonance imaging (MRI) (T2 map). The siRNA technique, enzyme-linked immunosorbent assay (ELISA), immunofluorescence staining and western blotting were performed to explore the potential mechanism of TM treatment. The number of microthrombi in the hippocampus microvessels was also recorded. TM significantly decreased brain water content and Evans Blue content, alleviated brain edema and neurological deficits after SAH. The plasma concentration of activated protein C was increased after TM treatment. In addition, the levels of phospho-p38MAPK, phospho-p53, cleaved caspase-3, phospho-NF-κB (p65) were markedly decreased. Additionally, the loss of VE-cadherin and Occludin (markers of vascular integrity) and the number of microthrombi in the hippocampus were also reduced. Our results indicated that TM has protective effects on preserving microvascular integrity following SAH partly through preserving endothelial junction proteins and quenching apoptosis/inflammation in endothelial cells via blocking p38MAPK-p53/NF-κB (p65) pathway.